2020
DOI: 10.1080/2162402x.2020.1792036
|View full text |Cite
|
Sign up to set email alerts
|

Specific immune landscapes and immune checkpoint expressions in histotypes and molecular subtypes of sarcoma

Abstract: Soft tissue sarcomas are a group of rare and aggressive connective tissue neoplasms for which curative therapeutic opportunities are limited in advanced phase. Clinical trials assessing immunotherapy in these tumors have so far reported limited efficacy. The objective of this study is to provide a description of the immunologic landscape of sarcomas to guide the next clinical trials of immunotherapy in these diseases. The gene expression profile of 93 immune checkpoint (ICP) and membrane markers (MM) of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…The immunogenomic study also disclosed a strong correlation between functionally active macrophages and a worse prognosis of sarcoma patients [ 138 ]. These findings are consistent with an extensive gene expression profiling carried out in 253 STS showing that a M0-macrophage signature correlated with poor metastasis-free survival in all four sarcoma subgroups investigated (synovial sarcoma, myxoid liposarcoma, sarcoma with complex genomic and GIST) [ 140 ]. Intriguingly, unlike that observed for other tumours, the infiltration of M2-macrophages characterised either using CD163 gene or the Cibersort M2-Macrophage signature showed no significant prognostic correlation with any of the sarcoma subgroups investigated.…”
Section: Future Directionssupporting
confidence: 88%
See 1 more Smart Citation
“…The immunogenomic study also disclosed a strong correlation between functionally active macrophages and a worse prognosis of sarcoma patients [ 138 ]. These findings are consistent with an extensive gene expression profiling carried out in 253 STS showing that a M0-macrophage signature correlated with poor metastasis-free survival in all four sarcoma subgroups investigated (synovial sarcoma, myxoid liposarcoma, sarcoma with complex genomic and GIST) [ 140 ]. Intriguingly, unlike that observed for other tumours, the infiltration of M2-macrophages characterised either using CD163 gene or the Cibersort M2-Macrophage signature showed no significant prognostic correlation with any of the sarcoma subgroups investigated.…”
Section: Future Directionssupporting
confidence: 88%
“…Another immune cell population with immunosuppressive properties that may be targeted in sarcoma for therapeutic purposes is represented by Tregs whose increased intra-tumour infiltration was shown to correlate with a poor prognosis in cohort of various STS [ 142 ]. Recent data demonstrated high expression levels of ICOS and its ligand B7H2 (ICOSL) in GIST, an intercellular interaction promoting the expansion of Tregs that correlated with a poor prognosis in these tumours [ 140 ]. Therefore, exploitation of anti-ICOS antagonists, currently under investigation in the clinics (MEDI-570; NCT025250791), could be a promising therapeutic strategy to inhibit Tregs expansion in GIST patients.…”
Section: Future Directionsmentioning
confidence: 99%
“…A French study found that the immune landscape of STS is very heterogeneous, but strongly correlates to histologic subtype [65]. Recently, Petitprez et al [66,67] analysed the TME composition in four publicly available STS data sets with gene expression profiles, using the microenvironment cell populationecounter method.…”
Section: Biomarkersmentioning
confidence: 99%
“…Chakravarthy et al performed a pan-cancer methylation-based deconvolution of tumor samples and classified sarcomas as ‘immune cold’, characterized by low infiltrates of cytotoxic T-lymphocytes (CTLs) [ 12 ]. However, the notion that sarcomas are immune-quiescent tumors is challenged by an increasing number of studies [ 5 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have characterized the tumor microenvironment and immune profile of STS but there is limited knowledge about the specific immunogenicity in context of genomic alterations [ 5 , 22 , 23 , 31 ].…”
Section: Discussionmentioning
confidence: 99%